Assessment of austral autumn air–sea CO2 exchange in the Pacific sector of the Southern Ocean and dominant controlling factors - Mo, Ahra; Park, Keyhong; Park, Jisoo; Hahm, Doshik; Kim, Kitae; Ko, Young Ho; Iriarte, José Luis; Choi, Jung-Ok; Kim, Tae-Wook (Frontiers in Marine Science, 2023)
The factors that control the partial pressure of carbon dioxide (pCO2) in the Pacific sector of the Southern Ocean were investigated in April 2018, onboard the icebreaker, ARAON. The mean (± 1σ) of the sea surface pCO2 was estimated to be 431 ± 6 μatm in the north of the Ross Sea (NRS), 403 ± 18 μatm in the Amundsen–Bellingshausen Sea (ABS), and 426 ± 16 μatm in the western Antarctic Peninsula and Weddell Sea (WAP/WS). The controlling factors for pCO2 in the NRS appeared to be meridionally different based on the southern boundary of the Antarctic Circumpolar Current (SB; ~62.5°S in the Ross Sea). The sea surface pCO2 exhibited a strong correlation with salinity and the difference between the O2/Ar (ΔO2/Ar) values of the sample and air-saturated water in the north and south of the SB, respectively. The pCO2 in the ABS and western WAP/WS displayed a strong correlation with salinity. Furthermore, ΔO2/Ar and sea ice formation appear to be the dominant factors that control pCO2 in the Confluence Zone (CZ) and northern parts of WAP/WS. The estimated air–sea CO2 fluxes (positive and negative values indicate the source and sink for atmospheric CO2, respectively) range from 3.1 to 18.8 mmol m−2 d−1 in the NRS, −12.7 to 17.3 mmol m−2 d−1 in the ABS, and −59.4 to 140.8 mmol m−2 d−1 in the WAP/WS. In addition, biology-driven large variations in the air–sea CO2 flux were observed in the CZ. Our results are the most recent observation data acquired in austral autumn in the Southern Ocean.